Superfícies singulares e ondas de aceleração em misturas - Silva, Antonio Santos (1979)
Study singular surfaces and waves in mixtures. Surface motion is studied and a well motivated definition of displacement derivative is presented. First, singular surfaces for a single body are defined and the compatibility conditions are obtained in a way that is direct and intrinsec. After, the study is extended for mixtures and two applications are worked for aceleration waves in binary mixtures of inert constituents with common temperature: computation of the local velocities of propagation for a mixture of a rigid solid and a non viscous fluid and a mixture of an elastic solid and a non viscous fluid.